Museu Militar de Lisboa : proposta de reprogramação museológica - Marques, Maria da Conceição Martins Vieira, 1959- (2017)
This Proposal for the Reprogramming of the Military Museum of Lisbon is underpinned by the need for the reconfiguration of some spaces, favoring the concentration of public flows, with the opening of an entry / exit door, located on the southern facade of the building, overlooking the cruise terminal of Santa Apolonia, giving visibility to the building. This implies the relocation of the museum shop, creation of new social and exhibition spaces, with the offering of new themes and reintroduction of others. We can consider that: In first place, we should redesigning a more suitable lighting project, minimizing the effects of excessive natural and artificial light, favoring the richness of color given by the scenic decoration of spaces, focusing on a higher rotativity of cultural objects on display; Secondly, by establishing a connection to the genesis of the space, stressing out the importance of Caves Manuelinas while a visible material link to Tercenas das Portas da Cruz connected to the casting, production of gunpowder, manufacture and repair of military equipment. Emphasizing the actions of Military Engineers, Masters and Artifices that there developed their activities. Third, by strengthening the ties that link this Military Museum to King Carlos I heritage by underlining his legacy on providing the necessary conditions to develop this museum as a former landmark and a true ex-libris in the Portuguese cultural landscape of the late nineteenth century, early twentieth century. Reflecting the latest military history including : Portugal in World War II; modernization of the Portuguese army and integration into NATO; the wars overseas and the revolution of the 25th of April, 1974; the Portuguese Army today